Improving Students' Mental Health Through Self-efficacy in Solving Algebraic Form Problems Using the Mentorika Application - Ahmida, Nuzila Yuli Alfi; Sari, Dian Widya; Hidayah, Lutfi; Nur Rohmad, Dimas Teguh; Basir, Mochamad Abdul (Universitas Islam Sultan Agung, 2024)
In today's increasingly complex life situations, mental health problems can increase, especially among students in Indonesia. Mental health problems that occur in students are related to Self-efficacy regarding the potential they have in achieving something and in dealing with pressure in certain situations. Low Self-efficacy in adolescents can cause emotional and mental disorders. Based on this, this study aims to develop a mentor application to help improve students' mental health through Self-efficacy in solving algebraic form problems. This research was conducted at SMP Negeri 2 Kedungtuban, and the subjects of this study were 30 seventh-grade junior high school students. The research method used is Research and Development (R&D), and the ADDIE Model design is used. The results of data analysis show that the mentorika application is proven to be valid because it has a significant level of 0.000 < 0.005, feasible because all variables (statements) have a value of r count > r table, and effective because it meets the individual completeness test and classical completeness test, so it can be said that the mentorika application developed is effective in improving students' mental health through Self-efficacy in solving algebraic form problems. The evaluation results show that the effect of student confidence on improving mental health in solving algebraic form problems has increased significantly after using the Mentorika application. Keywords: Mental Health, Self-Efficacy, Algebraic Forms.